Long term effects of comprehensive cardiac rehabilitation in an inpatient and outpatient setting (Swiss Medical Weekly, 2011)
OBJECTIVES: To compare the long-term effects of comprehensive outpatient versus inpatient rehabilitation with respect to morbidity and mortality, as well as to changes in physical performance and physical activity. DESIGN: A total of 163 consecutive patients were enrolled for comprehensive cardiac rehabilitation (CCR) following a recent coronary event, to outpatient or inpatient CCR according to treatment preference because randomisation was accepted by only 4 patients. CCR was six hours per day for 4 weeks and consisted of exercise training, education, psychological support, and nutritional and occupational advice. Examinations were before, after and 12 months after CCR. Primary outcome measures were event-free survival with or without interventions, EFS-I or EFS, respectively, 12 months after rehabilitation RESULTS: Main patient characteristics were distributed equally in the cohorts. Results were adjusted by logistic regression for age, BMI, LV-function, exercise capacity and physical activity before the event. Adjusted EFS, EFS-I , overall survival and other morbidity outcome measures did not differ significantly. During CCR, physical activity was higher in outpatients, but this difference was not maintained in the follow up. Average physical activity was increased 12 month after CR with no difference between groups. CONCLUSION: Although influenced by patient preference, participation in either inpatient or outpatient CCR led to comparable results in terms of all-cause or cardiac overall survival, event-free survival and other secondary outcome measures like cardiac morbidity, physical performance and increased physical activity.